A3COSMOS: the dust attenuation of star-forming galaxies at z = 2.5–4.0 from the COSMOS-ALMA archive. Issue 4 (22nd November 2019) - Fudamoto, Yoshinobu; Oesch, P A; Magnelli, B; Schinnerer, E; Liu, D; Lang, P; Jiménez-Andrade, E F; Groves, B; Leslie, S; Sargent, M T
ABSTRACT: We present an analysis of the dust attenuation of star-forming galaxies at z  = 2.5–4.0 through the relationship between the UV spectral slope (β), stellar mass ( M * ), and the infrared excess (IRX = L IR / L UV ) based on far-infrared continuum observations from the Atacama Large Millimeter/sub-millimeter Array (ALMA). Our study exploits the full ALMA archive over the COSMOS field processed by the A3COSMOS team, which includes an unprecedented sample of ∼1500 galaxies at z ∼ 3 as primary or secondary targets in ALMA band 6 or 7 observations with a median continuum sensitivity of 126 $\rm {\mu Jy\, beam}^{-1}$ (1σ). The detection rate is highly mass dependent, decreasing drastically below log ( M * /M⊙ ) = 10.5. The detected galaxies show that the IRX–β relationship of massive (log  M * /M⊙ > 10) main-sequence galaxies at z  = 2.5–4.0 is consistent with that of local galaxies, while starbursts are generally offset by $\sim 0.5\, {\rm dex}$ to larger IRX values. At the low-mass end, we derive upper limits on the infrared luminosities through stacking of the ALMA data. The combined IRX– M * relation at $\rm {log\, ({\it M}_{\ast }/\mathrm{M}_{\odot })\gt 9}$ exhibits a significantly steeper slope than reported in previous studies at similar redshifts, implying little dust obscuration at log  M * /M⊙ < 10. However, our results are consistent with earlier measurements at z ∼ 5.5, indicating a potential redshift evolution between z ∼ 2 and z ∼ 6. Deeper observations targeting low-mass galaxies will be required to confirm this finding.